Pengaruh Pemupukan Bakteri Pelarut Fosfat Dan Dosis Batuan Fosfat Terhadap Ketersediaan Fosfor Pada Tanah Budidaya Tanaman Jagung (Zea Mays L.) Di Ultisol Kentrong - Yanti Ningtyas, Dewi Nurma; Fitriatin, Betty Natalie; Setiawati, Mieke Rochimi; Simarmata, Tualar (CV.ITTC INDONESIA, 2024)
The use of Ultisols for plant cultivation has constraints, namely the nature of the soil is acidic and the availability of phosphate for plants is low. The use of Rocks Phosphate (RP) and Phosphate Solubilizing Bacteria (PSB) can be used as an alternative to increasing the availability of phosphate for environmentally friendly plants. PSB has the potential to increase the solubility and availability of phosphate in plants. The increase in the availability of phosphate for plants can be through the enzyme phosphatase and organic acids produced by PSB. This study aims to examine the effect of the type of PSB consortium and the dose of Rocks Phosphate on P uptake and growth of maize in Ultisols from Kentrong. The research was conducted at the Ciparanje Experimental Garden, Faculty of Agriculture, Padjadjaran University, Jatinangor. The design used was a randomized block design with factorial pattern consisting of phosphate solubilizing bacteria (without the PSB consortium, exogenous PSB consortium, indigenous PSB consortium, and mixed consortium) and Rocks Phosphate dosage (100% SP-36, 100% RP, 80% RP, 60% RP) with three replications. The results showed no interaction between the type of PSB consortium and the dose of Rocks Phosphate. The results of the independent effect showed that the treatment of using SP-36 was the best treatment in available P.